'The costumes don't do it for me': Obstacles to the translation of 'new' management ideas. Issue 5 (November 2017) - McCabe, Darren; Russell, Stephanie
It has been argued that management support is important to successfully translate new management ideas into practice. Through focusing on the obstacles to the translation of a management guru text in a manufacturing organisation, we point towards a far more uncertain situation. First, we explore the paradoxical situation of engaged managers undermining the implementation of new ideas. Second, we consider how attempts to use humour to aid translation may generate a variety of unintended employee translations. Third, we examine how the objects that management enlist to support translation can thwart change. It has been argued that 'technological' and 'textual' objects exercise agency through making humans act in intended ways. Into this mix, we add 'cultural' objects (in our case costumes) and argue that while they exercise agency, the outcomes they produce may hinder managerial designs.